(untitled) (Forum Penelitian Agro Ekonomi, 2024)
Agroforestry is developed to offer benefits to the nearby communities. It also aims at producing food. Improving food production could be carried out through an extensification program, such as an agro forestry system. Ministry of Forestry also takes a part in national food security through agro forestry where it is an intercropping between food crops and forest trees. Agro forestry is run using a Community-Based Forest Management (PHBM). To integrate forest preservation and community development, PHBM facilitates establishment of Forest Village Community Organization (LMDH). Agro forestry commonly involves LMDH contributes to 41.32 percent of the households’ income and creates employment of 2.39 persons per hectare. Agro forestry is effective in improving income distribution, households’ income, food production, and poverty alleviation in the communities nearby the forests.